`int x/sqrt(x^2+6x+12) dx` Complete the square and find the indefinite integral

Expert Answers

An illustration of the letter 'A' in a speech bubbles

Recall indefinite integral follows `int f(x) dx = F(x)+C`


`f(x)` as the integrand

`F(x)` as the antiderivative of `f(x)`

`C` as the constant of integration.

To evaluate the given integral:  `int x/sqrt(x^2+6x+12)dx` , we  may apply completing the square at the trinomial: `x^2+6x+12` .

Completing the square:

`x^2+6x+12` is in a form of `ax^2 +bx+c`


`a =1`

`b =6`

 `c= 12`

 To complete square ,we add and subtract `(-b/(2a))^2` :

With `a=1 ` and `b = 6` then:

`(-b/(2a))^2 =(-6/(2*1))^2 = 9`

Then `x^2+6x+12` becomes:

`x^2+6x+ 12 +9-9`

`(x^2+6x+9) + 12 -9`

`(x+3)^2 +3`

Applying `x^2 +6x +12 =(x+3)^2 + 3` in the given integral, we get:

`int x/sqrt(x^2+6x+12)dx=int x/sqrt((x+3)^2 + 3)dx`

We may apply u-substitution by letting:  `u = x+3` or` x =u-3` then `du = dx` .

The integral becomes:

`int x/sqrt((x+3)^2 + 3)dx =int (u-3)/sqrt(u^2 + 3)du`

Apply the basic integration property: `int (u-v) dx = int (u) dx - int (v) dx` .

`int (u-3)/sqrt(u^2 + 3)du =int u/sqrt(u^2 + 3)du -int 3/sqrt(u^2 + 3)du`

For the integral of  `int u/sqrt(u^2 + 3)du` , we may apply formula from integration table: `int u/sqrt(u^2+-a^2) du = sqrt(u^2+-a^2) +C`

Take note we have + sign inside the root then we follow: `int u/sqrt(u^2+a^2) du = sqrt(u^2+a^2) +C` .

`int u/sqrt(u^2 + 3)du=sqrt(u^2+3) `                         

For the integral of `int 3/sqrt(u^2 + 3)du` , we use the basic integration property: `int cf(x)dx = c int f(x) dx.`

`int 3/sqrt(u^2 + 3)du = 3int 1/sqrt(u^2 + 3)du`

From integration table, we may apply the formula for rational function with roots:

`int 1/sqrt(x^2+-a^2)dx = ln|x+sqrt(x^2+-a^2)| +C`

With just `(+)` inside the root, we follow:`int 1/sqrt(x^2+a^2)dx = ln|x+sqrt(x^2+a^2)| ` +C.

`3int 1/sqrt(u^2 + 3)du=ln|u+sqrt(u^2+3)|`

Combining the results, we get:

`int (u-3)/sqrt(u^2 + 3)du =sqrt(u^2+3) -ln|u+sqrt(u^2+3)| +C`

Plug-in `u = x+3` on `sqrt(u^2+3) -ln|u+sqrt(u^2+3)| +C` , we get the indefinite integral as:

`int x/sqrt(x^2+6x+12)dx =sqrt((x+3)^2+3) -ln|x+3+sqrt((x+3)^2+3)| +C`

Recall: `(x+3)^2+3 =x^2+6x+12` then the indefinite integral can also be expressed as:

`int x/sqrt(x^2+6x+12)dx =sqrt(x^2+6x+12) -ln|x+3+sqrt(x^2+6x+12)| +C`

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial